Investigation The Influences of Electric Motor and Electric Go Kart Performance - Arshad, Mohd Fitri; Ahmad, Muhammad Faris; Khalid, Amir; Ishak, Izuan Amin; Zainal Abidin, Shaiful Fadzil; Razali, Mohd Azahari (Journal of Automotive Powertrain and Transportation Technology, 2023)
This researcher focused at every type of electric motor and every force applied to a go kart. The goal of this research is to choose a prototype of an electric motor drive mechanism and test its performance on an electric go-kart. Furthermore, the purpose of this study is to establish the power requirements of an Electric Go-Kart, as well as its specific motion capabilities and performance specifications factors, in order to access the performance of the Electric Go-Kart motion. The benefit of developed electric go kart is to help decrease the pollution emitted and as a substitute to the typical combustion engine vehicle. However, due to its high congestion and pollution issue, a pollution with free vehicle created. In the first phase of the project, the researcher surveyed information related to the typical of electric motor that use in electric go kart. The second phase of the project is mainly on calculating the forces acted on the Electric Go Kart itself. Three main factor of movement behavior on go kart determined rolling resistance 54.88N, air resistance 28.4N and force gravity going uphill 552.98N. After that, the researcher selects drive system components with required specifications. The Brushless DC Motor was selected with 2000W 48V whose maximum output torque is 27.6Nm. Towards the end phase of the project, the electric go kart prototype was developed with actual size of go kart 1.94m length, 1.4m width and 0.5m height. Electric motor was analyzed on the motor speed, torque and power to make sure that the performance was approximately the set specifications. In conclusion, the project was success and it can produce a good performance at the go kart.